A pressure vessel for studying gas foaming of thermosetting polymers: sorption, synthesis and processing. (September 2017) - Di Caprio, Maria Rosaria; Tammaro, Daniele; Di Maio, Ernesto; Cavalca, Sara; Parenti, Vanni; Fangareggi, Alberto; Iannace, Salvatore
Abstract: We herein report the design of an apparatus for studying the concurrent chemo-physical processes occurring during gas foaming of thermosetting polymers. In particular, to address the recent interest in combining the gas (physical) foaming with the classical (chemical) polyurethane foaming, a novel instrumented pressure vessel was designed for investigating: i) gas sorption under high pressure on the different reactants, kept separate; ii) synthesis under high gas pressure, upon mixing and iii) foaming upon release of the pressure. The design of the new pressure vessel relies on two key features. From the processing side, we make use of a rubber impeller to keep the two reactants separate during gas sorption and to allow for an efficient mixing at the end of the sorption stage. From the analytic side, we utilized a sapphire window beneath the sample holder to use diffuse reflectance near-infrared spectroscopy to measure both the amount of sorbed gas and the reaction kinetics under gas pressure. Preliminary results are reported for the polyol-isocyanate/CO2 system.